Under the cover of mercy : a novel - Connolly, Rebecca (Shadow Mountain Publishing, 2023)
"Can one nurse on a mission of mercy and rebellion turn the tide of WWI? November 1914--The Great War has come to Brussels, and Edith Cavell, Head Nurse at Berkendael Medical Institute, faces an impossible situation. She has sworn an oath to help any who are wounded, under whatever flag they are found. But Governor von Lüttwitz, the ranking German officer, has ordered her and her nurses to also stand guard over the wounded Allied prisoners of war and prevent them from escaping. Edith feels that God called her to be a healer, not a jailer. How can she heal these broken boys, only to see them returned to the hands of their oppressors to be beaten again? So when members of the Belgian resistance, desperate for help, bring two wounded British soldiers to her hospital in secret, she decides she will heal the soldiers, and then help smuggle them out of the hospital to freedom. With her loyal friend and fellow nurse, Lizzie, by her side, Edith establishes her hospital as a safe house for the resistance, laboring tirelessly to save as many soldiers as she can. Working under the watchful eyes of the German army, Edith faces challenging odds as she fights to bring hope to her small corner of a war-torn world. Based on a true story, Under the Cover of Mercy is the remarkable account of one woman who defied an entire nation in order to heal those who needed her help the most.. "--